1967
DOI: 10.1079/bjn19670068
|View full text |Cite
|
Sign up to set email alerts
|

Protein reserves and muscle constituents of protein-depleted and repleted cocks

Abstract: I . Body-weight changes and nitrogen balance were studied, together with the concentration of various nitrogenous muscle components, in adult cocks before and after a 6-day period on a N-free diet and again after a 16-day repletion period on diets supplying various amounts and types of dietary N. 2.In the first experiment a comparison was made during the repletion period between a fish-protein supplement and a supplement of glycine + glutamic acid added to an essential amino acid mixture.3. During the depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1969
1969
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…One of the most noteworthy biochemical alterations in muscles of protein-deprived animals is a redueti011 in WNA content. This response has been observed by many investigators (Masters 1963 ;Ashley and Fisher 1967;Young and Alexis 1968;Pond ef al. 1969;Hill et cal.…”
Section: Itlals Work Was Supported By the Medical Researchsupporting
confidence: 51%
“…One of the most noteworthy biochemical alterations in muscles of protein-deprived animals is a redueti011 in WNA content. This response has been observed by many investigators (Masters 1963 ;Ashley and Fisher 1967;Young and Alexis 1968;Pond ef al. 1969;Hill et cal.…”
Section: Itlals Work Was Supported By the Medical Researchsupporting
confidence: 51%
“…Although these studies shed little light on the nature of the retained N, they do indicate that nonessential N can and does play an important role in intermediary N metabolism in the body. As a follow-up to the investigation just cited, additional adult cocks were N-depleted on a protein-free diet (Ashley and Fisher, 1967). One group was fed a maintenance mixture of essential amino acids only, which constitutes an inadequate amount of total N; a second group was given the same diet but with additional N in the form of aspartic acid to meet not only the maintenance needs for essential amino acids but also the total N needs to permit repletion.…”
Section: Hans Fishermentioning
confidence: 99%
“…The higher level of lysine in the liver obtained in the OL group is similar to the results of Dalgliesh and Tabechian (1956) who observed that after a labelled amino acid solution had been administered to rats by stomach tube, the activity of the 'protein-bound' fraction in liver, as well as in muscle, increased. In the past few years many reports have given attention to the controversial concept of labile body protein reserves contributing to the free amino acid pools of the body (Holt, Halac and Kajdi, 1962;Holmes, 1965;Fisher, 1967;Munro, 1964;Yuile, Lucas, Neubecker, Cochrane and Whipple, 1959;Ashley and Fisher, 1967;Allison, Wannemacher, Banks and Wunner, 1964). Results of an investigation on dogs reported by Van Slyke and Meyer (1913a, b) also show that musculature is the major reservoir of amino acids, although the percentage content of amino acids in muscle is less than in liver compared with the normal dogs.…”
Section: Ratio Ofmentioning
confidence: 99%